Being a Muslim in Animistic Ways - Maarif, Samsul (Al-Jamiah: Journal of Islamic Studies, 2014)
This paper examines religious practices of Ammatoans professed to be âIslamicâ by practitioners, but ethnocentrically understood as âanimisticâ in Tylorian sense by scholars. Scholars have argued that Ammatoansâ practices are incompatible with Islam. Islam and animism are mutually exclusive. This paper, in contrast, argues that Islam and animism are all encompassing. To build the argument, this paper firstly elaborates scholarsâ revisited theory of animism that argues for the (indigenous) notion of personhood as not limited only to human beings, but extended to non-human beings: land, forest, trees, animals and so forth. Secondly, this paper reviews the Quranic verses that explicate the personhood of non-human beings, and finally Ammatoansâ practices âvisits to forest, refusal of electricity installation and othersâ as ethically responsible and mutually beneficial acts that ensure the well-beings of both human and non-human beings (interpersonal relations). These presentations show how Ammatoans exemplify being Muslim in animistic ways.[Artikel ini membahas praktik keagamaan masyarakat Ammatoa, yang menurut pelakunya disebut âIslamicâ, tetapi menurut ahli etnografi sering disebut animistik, karena tidak sesuai dengan ajaran Islam. Islam dan animisme saling menafikan. Namun hasil penelitian ini membuktikan lain, Islam and animisme saling terkait dan saling mengisi. Untuk mengawali pembahasan, dipaparkan pandangan para ahli mengenai konsep âbaruâ anismisme yang memandang konsep dasar tentang diri tidak hanya terbatas pada manusia, tetapi juga mencakup selain manusia: tanah, hutan, pohon, hewan, dan lain-lain. Ayat-ayat al-Quran juga memperkenalkan adanya konsep diri bagi selain manusia. Baru kemudian dibahas mengenai praktik-praktik masyarakat Amatoa, seperti masuk hutan, menolak instalasi listrik, dan lainnya, yang merupakan tanggung jawab moral serta bermanfaat bagi kehidupan, baik bagi manusia maupun selain manusia dalam konteks hubungan interpersonal. Paparan ini menunjukkan corak khas masyarakat Ammatoa untuk menjadi seorang muslim dalam cara yang animistik.]